An action research in bringing improvements in the work from home (WFH) experience of a regional business team through effective employee experience programs - Pineda, Aries John S. (Animo Repository, 2021)
Given the mandate of the senior leaders of TGT company to ensure business recovery during General Community Quarantine (GCQ), the regional business team needs to ensure that its most important enabler, which is our people are empowered and motivated in their work assignments. But the changes in the work setting, from a traditional workplace to working from home (WFH) cause many challenges in the lives of our employees, both personal and professional. The collaborators conducted this action research to address the need to improve the employees’ work from home experience through effective employee experience programs supported by a critical realist approach in the whole two cycles. The first cycle is about handholding employees with the changes and keeping them motivated, whereas Kotter’s change model and Maslow’s hierarchy of needs were utilized respectively. The second cycle is about institutionalizing effective WFH experience programs by which Eisenhower Matrix in decision making was used. ADDIE, a process model in training and program design was used in both cycles and complimented with IBM’s five best practices in designing effective employee experience during the second cycle. The collaborators together with the Mindanao leadership team (MLT) and its HR business partner were able to institutionalize the Mindanao WFH employee experience program, which is now part of the MLT’s people excellence pillar. This action research gave the collaborators a wonderful journey to create a humane working experience and common good in the organization which is aligned with RVR COB Code of Ethics for Business. Keywords: bringing improvements, work from home, employee experience